Comparative benchmarks of full QCD algorithms - Frezzotti, Roberto; Hasenbusch, Martin; Wolff, U.; Heitger, Jochen; Jansen, Karl (Computer physics communications, 2001)
We report performance benchmarks for several algorithms that we have used to simulate the Schrödinger functional with two flavors of dynamical quarks. They include hybrid and polynomial hybrid Monte Carlo with preconditioning. An appendix describes a method to deal with autocorrelations for nonlinear functions of primary observables as they are met here due to reweighting.